Oncogene-induced senescence and its evasion in a mouse model of thyroid neoplasia. (15th January 2018) - Bellelli, Roberto; Vitagliano, Donata; Federico, Giorgia; Marotta, Pina; Tamburrino, Anna; Salerno, Paolo; Paciello, Orlando; Papparella, Serenella; Knauf, Jeffrey A.; Fagin, James A.; Refetoff, Samuel; Troncone, Giancarlo; et al.
Abstract: Here we describe a conditional doxycycline-dependent mouse model of RET/PTC3 (NCOA4-RET) oncogene-induced thyroid tumorigenesis. In these mice, after 10 days of doxycycline (dox) administration, RET/PTC3 expression induced mitogen activated protein kinase (MAPK) stimulation and a proliferative response which resulted in the formation of hyperplastic thyroid lesions. This was followed, after 2 months, by growth arrest accompanied by typical features of oncogene-induced senescence (OIS), including upregulation of p16INK4A and p21CIP, positivity at the Sudan black B, activation of the DNA damage response (DDR) markers γH2AX and pChk2 T68, and induction of p53 and p19ARF. After 5 months, about half of thyroid lesions escaped OIS and formed tumors that remained dependent on RET/PTC3 expression. This progression was accompanied by activation of AKT-FOXO1/3a pathway and increased serum TSH levels.